2022
DOI: 10.1175/bams-d-21-0232.1
|View full text |Cite
|
Sign up to set email alerts
|

A Collaborative Effort to Better Understand, Measure, and Model Atmospheric Exchange Processes over Mountains

Abstract: In this essay, we highlight some challenges the atmospheric community is facing concerning adequate treatment of flows over mountains and their implications for numerical weather prediction (NWP), climate simulations and impact modeling. With recent increases in computing power (and hence model resolution) numerical models start to face new limitations (such as numerical instability over steep terrain). At the same time there is a growing need for sufficiently reliable NWP model output to drive various impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…On the other hand, although we have been able to provide highly resolved cross-valley transects of z i and w L , our conclusions were nonetheless restricted to having just three discrete sites offering H. To truly explore the CBL growth framework, similar highly resolved transects of H are necessary, a demand potentially fulfilled with an array of carefully sited scintilometers (Ward, 2017). We are confident that the upcoming Multi-scale Transport and Exchange Processes in the Atmosphere over Mountains (TEAMx) programme and experiment (Serafin et al, 2020;Rotach et al, 2022) will offer the necessary means and resources to address these remaining challenges.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…On the other hand, although we have been able to provide highly resolved cross-valley transects of z i and w L , our conclusions were nonetheless restricted to having just three discrete sites offering H. To truly explore the CBL growth framework, similar highly resolved transects of H are necessary, a demand potentially fulfilled with an array of carefully sited scintilometers (Ward, 2017). We are confident that the upcoming Multi-scale Transport and Exchange Processes in the Atmosphere over Mountains (TEAMx) programme and experiment (Serafin et al, 2020;Rotach et al, 2022) will offer the necessary means and resources to address these remaining challenges.…”
Section: Discussionmentioning
confidence: 96%
“…Here we focus on dry rather than on moist convection, as the latter often results in deep, precipitous convective cells (Kirshbaum et al, 2018), thereby perturbing the gentle balance of quiescent conditions necessary for fairweather development of CBL and MoBL. While the assumption of vertical exchange being responsible for the majority of convectively-driven turbulence in the CBL is acceptable over HHF terrain, this cannot be expected to hold over complex terrain, where horizontal motions and associated effects become increasingly more important to consider (Rotach et al, 2015(Rotach et al, , 2022Lehner and Rotach, 2018). In addition, a multitude of non-turbulent transport mechanisms are made possible by the presence of mountain chains (Whiteman, 2000;Zardi and Whiteman, 2013;De Wekker and Kossmann, 2015;Serafin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…2022 ), and the upcoming TEAMx program (Multi-Scale Transport and Exchange Processes in the Atmosphere over Mountains-Program and Experiment; Rotach et al. 2022 ) in highly complex, mountainous terrain will provide important observational data for future model evaluation studies. Already ongoing model intercomparison studies in the framework of TEAMx, in which both WRF and GRAMM-SCI are participating, will also shed further light on the performance of mesoscale models in mountainous areas and help to identify and hopefully improve existing deficiencies.…”
Section: Discussionmentioning
confidence: 99%
“…Besides basic meteorological variables and in situ fast-response measurements of wind, temperature, water vapour and carbon dioxide, many trace gases and aerosols are also observed (e.g. Karl et al, 2017;Deventer et al, 2018;Karl et al, 2018), in addition to vertical profiles of wind using a Doppler lidar (Haid et al, 2020(Haid et al, , 2021 and temperature and humidity using a microwave radiometer (Rotach et al, 2017). The focus of this study is on the surface-atmosphere exchange of momentum, heat and mass observed using the eddy covariance (EC) technique.…”
Section: Site Descriptionmentioning
confidence: 99%
“…a cool sea breeze versus warm foehn; Hirsch et al, 2021). There is a real need for turbulence observations to develop process understanding, evaluate model performance and improve predictive capabilities in complex terrain, particularly when meteorologically based tools and expertise are used to inform planning or policy decisions that have direct consequences for human and environmental health (Rotach et al, 2022). Measures that have been successfully applied to other cities may have inadvertent effects when applied to a different city, especially one with very different surroundings.…”
Section: Introductionmentioning
confidence: 99%